Correlation Between Lactate Dehydrogenase (LDH) Values and Aspects Score at the Beginning of Treatment in Acute Ischemic Stroke - Fikriyah, Lathifatul (Jurnal Health Sains, 2025)
Stroke is the second leading cause of death worldwide, with ischemic stroke comprising 87% of cases. Metabolic acidosis from hypoxia promotes anaerobic glycolysis, raising lactate dehydrogenase (LDH) levels, which reflects neuronal tissue injury and inflammation in acute ischemic stroke. The Alberta Stroke Program Early CT Score (ASPECTS) is used to assess ischemic brain injury on non-contrast CT, aiding early prognosis and treatment decisions. This cross-sectional study at Dr. Soetomo Hospital, Surabaya (February–May 2023), included 30 acute ischemic stroke patients (53.3% male, mean age 60.2 ± 7.1 years, onset 2–5 days). Exclusion criteria were prior thrombolysis, cancer, or organ failure. LDH levels were measured at admission using the Alinity C analyzer, and ASPECTS was calculated from initial CT scans. Spearman’s correlation was used for analysis. Results showed a significant inverse correlation between LDH and ASPECTS (r = -0.279, p = 0.003), indicating that higher LDH levels correspond with lower ASPECTS (larger infarcts). Mean LDH was elevated (258.75 ± 50.65 U/L, normal 120–190 U/L). Comorbidities included hypertension (90%), dyslipidemia (83.3%), and diabetes mellitus (56.7%). These findings suggest that serum LDH may be a valuable adjunct biomarker for early assessment of ischemic stroke severity when advanced imaging is unavailable, helping clinicians estimate infarct size rapidly. Further research involving larger populations is recommended to confirm LDH’s utility and to examine its combination with other biomarkers for acute ischemic stroke management.